Sports Management and Sports Humanities - Kanosue, Kazuyuki; Kogiso, Kohei; Oshimi, Daichi; Harada, Munehiko (Springer Japan : Imprint: Springer, 2015)
This book focuses on (1) sports management, (2) sports economics and policy, and (3) sports humanities. The fact that sports humanities is a part of the sports management education program means that a person with extensive knowledge-not only business-related comprehension but also acquaintance with art-related fields, such as the humanities and law-will play a central role in sports management in the next generation. The former two parts aim to provide a clear understanding of sports management and marketing, including the motivational and/or emotional components of fan behavior and sports participation, sports club management, sports sponsorship, athlete reputation management, sports economics, and elite sports policy. As stated above, various topics can be found in sports management research from the macro to the micro point of view, and they are not individually separated but intimately connected. Moreover, given the interdisciplinary nature of sports management, specific, common, and cross-border issues arise in each country. Data from several countries are included in the sports management part. Research beyond borders and collaborative research are expected to increase more significantly than before. Researchers in sports management are expected to find the best answers to such questions as how to manage sports-related organizations or people effectively, how to stimulate the global or local economy and exert social impact through sports, and how to help people gain well-being through sports. These research questions have not changed all through the ages and across the globe. In this book, the researchers also try to find the optimized solution in each topic, and readers can find traces of their passionate exploration.